Pensar nos bichos : afetos e políticas da proteção animal - Oliveira, Guilherme Antunes de (2012)
As an ethnography about interspecific relationships – between humans and animals – in urban contexts, this dissertation aims to reflect about the actions related to the management and protection of animal life within institutional and domestic scopes. From the contact with activist groups in two cities in the state of São Paulo it was possible to observe situations that alternate between containment and propitiation measures and their consequent interferences in a conviviality supported by the principle of animal protection. Government and activism – as well as the perceptions and conceptions of the domestic animal resulting from their respective actions – allow a theoretical and methodological reflection on the binomial established between culture and nature, when they reveal conflicts and possible ambivalences of animal protection, situated between control and hosting measures that, consequently, are linked to affectivities and legal issues. Ethical arguments, contained in laws and public policies, as well as the appeal to the sensitive dimension, eventually triggered by activism, also provide subsidies to understanding other concepts - such as welfare and animal rights – and these interspecific relationships mediated by emotions and reason, both tangents to the moral condition of the animal as part of a predominantly human socius.